Pengaruh Brand Image, Brand Awareness dan E-WOM (Electronic Word Of Mouth) Terhadap Keputusan Pembelian Merché (Studi Kasus Pada Mahasiswa FEB Universitas Islam Malang) - Hamida, Rahma Nur’aini; Nurhajati, Nurhajati; Rahmawati, Rahmawati (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This research aims to identify and analyze the influence of brand image, brand awareness, and E-WOM (electronic word of mouth) on purchasing decisions for Merché among students of the Faculty of Economics and Business at the Islamic University of Malang. The research method used is a quantitative approach with an explanatory research design. The sampling technique employed was purposive sampling, with a total of 75 respondents. Data analysis was conducted using multiple linear regression analysis with SPSS 29 software. The results of this study indicate that 1) Brand Image does not have a significant effect on purchasing decisions, 2) Brand Awareness has a significant effect on purchasing decisions, and 3) E-WOM (Electronic Word of Mouth) has a significant effect on purchasing decisions. Keywords: Purchasing Decisions, Brand Image, Brand Awareness, E-WOM (Electronic Word Of Mouth)